Rubber Based Bionanocomposites Preparation - Visakh P. M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Leading researchers from industry, academy, government and private research institutions across the globe have contributed to this book, which presents all types of rubber blend composites based on biomaterials as well as nanocomposites. It discusses the fundamental preparation methods of these materials and summarizes many of the latest technical research advances, offering an essential guide for academics, researchers, scientists, engineers and students alike. .
Rubber based Bionanocomposites: Preparation State of Art -- Cellulose based Rubber Nanocomposites -- Cellulose in rubber based blends and micro composites -- Chitin based Rubber Nanocomposites -- Chitin based Rubber Nanocomposites -- Starch based rubber nanocomposites -- Starch in rubber based blends and micro composites.
Keywords: Ceramic materials; Microtechnology; Microelectromechanical systems; Bioorganic chemistry; Biomaterials; Ceramics; Microsystems and MEMS; Bioorganic Chemistry; Biomaterials